Time-Dependent Features of Mass Transfer and Transmembrane Potential in Erythrocytes During Equilibration in Cryoprotective Solutions - Todrin, Oleksandr; Timofeyeva , Olena; Gordiyenko, Olga (Problems of Cryobiology and Cryomedicine, 2023)
On the basis of the developed physical and mathematical model of mass transfer, which takes into account the transmembrane transfer of non-electrolytes, basic ions and the associated changes in the transmembrane potential, the redistribution of osmotically active substances during equilibration of erythrocytes in cryoprotective solutions was investigated. Time parameters of changes in concentrations of osmotically active substances inside and outside cells, as well as transmembrane electric potential, were calculated. It is shown that during the exposure of human erythrocytes to 1M solutions of glycerol, 1,2-propanediol (1,2-PD) and dimethylsulfoxide (DMSO), the sign of their transmembrane electric potential changes three times, and in solutions of ethylene glycol (EG) and of acetamide (AA) – once. The analysis of the obtained results showed that the most acceptable for further cryopreservation from the point of view of erythrocytes reaching a state close to equilibrium in a 1M solution of glycerol was their equilibration for 5.5 min, and in solutions of DMSO, AA, EG and 1,2-PD with the same concentration – 1 min. At the same time, the cells remain somewhat dehydrated (by 5.5–7.5%), and the concentrations of cryoprotectants inside erythrocytes change insignificantly during longer exposure. The indicated degree of dehydration does not affect cell viability, but reduces the likelihood of intracellular ice formation during subsequent freezing. Probl Cryobiol Cryomed 2023; 33(2):103–114